Balancing Professional Standards and Political Discretion in Selecting Top Officials in Slovenia - Polonca KOVAČ (Transylvanian Review of Administrative Sciences, 2013)
One of the key drivers of modern and efficient public administration under the good governance doctrine is an efficient top officials’ selection system. A targeted selection and recruitment system is a prerequisite for the whole administration to act in compliance with the political priorities of the government. However, civil servants and top officials alike must put professional competencies above political loyalty. Therefore, a new system was introduced in Slovenia following the 2003 Civil Servants Act, aimed at ensuring professionalism against (over)politicization of public administration. A research carried out in 2012 among candidates and selected top officials and ministers, as their political superiors, revealed an overall efficiency of the Slovenian selection scheme in the sense of restricted over-politicization and increased professionalism. Its outcomes lead to the conclusion that the selection system in Slovenia, owing to its two-phase professional and political selection, is most adequate in terms of both regulation and practice since it takes into account the twofold role of top officials and civil service or public administration as a whole (first, as a force providing professional solutions by ensuring legality and efficient resource management, and second, as the closest collaborators of the political leadership implementing government policies).